The Relationship Between Work Engagement and Work Motivation with Job Satisfaction Among Warehouse Employees at PT. Duro Bangun Indonesia in East Jakarta - Joko Andi Nugraha; Evah Holifah; Hanifa Muslima; Zainun Mu'tadin (Eduvest - Journal of Universal Studies, 2026)
The purpose of this study is to examine the relationship between work engagement and job satisfaction, the relationship between work motivation and job satisfaction, and the combined relationship between work engagement and work motivation with job satisfaction among warehouse employees at PT. Duro Bangun Indonesia in East Jakarta. This research employs a quantitative method. The subjects are part-time warehouse employees at PT. Duro Bangun Indonesia in East Jakarta, with a total population of 35 employees. The research sample was selected using simple random sampling. The measuring instruments for this research include three scales: the Job Satisfaction Scale, the Work Engagement Scale, and the Work Motivation Scale. The results reveal a significant positive relationship between work engagement and job satisfaction (, , ). Similarly, there is a significant positive relationship between work motivation and job satisfaction (, , ). Furthermore, work engagement and work motivation together significantly predict job satisfaction (, , ), accounting for or 33.7% of the variance. This indicates that approximately 66.3% of the variance is attributable to other unidentified factors.